FEATURES OF MODERN CURRENT OF REACTIVE ARTHRITIS IN CHILDREN - Klimenko, V.A.; Савво, В.М.; Yanovska, K.O. (World of Medicine and Biology, 2014)
It was defined clinical and laboratory characteristics of modern current of reactive arthritis in children. The children were divided by age, divided into three age groups. It was assessed complaints, physical examination findings, blood chemistry, IEA for determining the trigger infections. There were identified three variants of reactive arthritis: urogenital, postrespiratory and arthritis after nasopharyngeal infections.